The rocky road to biomolecules. (6th December 2018) - Baross, John A.
A natural chemical reaction that occurs below the sea floor makes the amino acid tryptophan without biological input. This finding reveals a process that might have helped life on Earth to begin. An amino acid can be made naturally without requiring biological input.